Entreprenuerial intention among business undergraduates in Universiti Teknologi MARA Kampus Bandaraya Melaka / Nur Hanisa Mustafea - Mustafea, Nur Hanisa (Faculty of Business and Management, 2019)
The main purpose of this study is to analyze the entrepreneurial intention of business undergraduates in UiTM Malacca, City Campus who major in international business courses. Since most literature agreed that entrepreneurial intention can be determined by using Theory of Planned Behaviour (TPB) by Ajzen (1991, thus the study used the Theory of Planned Behaviour by Ajzen (1991) to identify the factors that influence business undergraduate whether they have an intention to pursue into entrepreneurship. Using survey method, 110 responses were analyzed to test the hypothesis, hence achieve the objectives of the study. The researcher distributed the questionnaire to collect 110 responses from specifically among international business undergraduates students in UiTM Kampus Bandaraya Melaka and data collected were analysed by Statistical Packages for Social Science (SPSS). The findings of the study also found out of these three factors, attitude toward behavior emerged as the strongest factor that had a strong influence and subjective norm fails to generate a significant impact on entrepreneurial intention among business undergraduates in UiTM Kampus Bandaraya Melaka. The study hopes to assist the responsible parties that involve in the effort to encourage the entrepreneurial activities for example the university in developing and producing more graduates that have high interests on entrepreneurship.